KAJIAN UMUM TENTANG TINDAK KEKERASAN DALAM RUMAH TANGGA - Ahmad Sainul (IAIN Padangsidimpuan, 2021)
From some of the explanations above, several conclusions can be drawn, including: Violence in household is human behavior (a person / group of people) that can cause suffering to others (individuals / groups). Meanwhile, forms of violence in household can be in the form of physical violence or psychological violence. Including physical violence is intercourse with a wife who is menstruating or forcing sexual intercourse.One example of domestic violence in terms of forced sexual intercourse includes: Forcing sexual intercourse when the wife is not ready or in her period. Sexual intercourse accompanied by torture, and Coercion of sexual intercourse in a way that the wife does not wantAllah forbids husband and wife relations when the wife is menstruating, because menstrual blood contains arsenic, iodine, and phosphorus. Menstruation is like a way to cleanse a woman's body and free it from toxins and impurities. Having intercourse with women while they are menstruating brings disease and dangers to both men and women